ANALYSIS OF LEARNING STRATEGIES FOR STUDENTS WITH SPECIAL NEEDS (ABK) - Fajrina, Rahmawati Lita; Rofiq, Mohammad (PD PGMI se Indonesia, 2024)
This study examines the analysis of learning strategies and obstacles for ABK at MI Darul Ulum Wates. The purpose of this study is to identify the most effective strategies and obstacles faced in supporting development and learning. The research approach applied to the research is qualitative descriptive. Interviews, documentation studies, and observational methods are all used in the data collection process. The data reduction procedure, data presentation, and conclusion reached are among the data analysis approaches used. The results of this study show that (1) this school accepts children with special needs as long as the school can still overcome it, (2) the learning strategy applied in this school uses the lesson repetition strategy, (3) the obstacles experienced are the limited competence of teachers in educating students with special needs, experience delays in receiving learning materials taught by teachers, the absence of special facilities and infrastructure, such as various learning tools or support provided by the government for services for students with special needs. The implications of this study are ramifications include the necessity of enhancing teacher proficiency in instructing children with special needs (ABK) and the requirement for specialized infrastructure and resources to assist the learning process.